Examining the value of money in america over the long term (1792–2009) - Abdullah, Adam (Canadian Center of Science and Education, 2013)
This paper aims to examine the significant loss of value of money over the long term in America between 1792–2009. One U.S. dollar in 1792 is now worth only two cents by 2009. By critically examining the value and purchasing power of money in America, this paper compares empirical evidence and statistics through long term analysis of gold, silver and commodity price indices, as to which medium of exchange provides for the best store of value. This paper finds that monetary policy should not target stable prices, by managing the quantity or purchasing power of money, but instead adopt a monetary theory of value involving a stable currency, free of any monetary management or manipulation, permitting a stable purchasing power and thus stable prices.